A novel pThr217 tau monoclonal antibody reveals neuropathological heterogeneity in tauopathies - Giavanna Paterno; Brach M. Bell; Kimberly-Marie M. Gorion; Stephan Quintin; Stefan Prokop; Benoit I. Giasson (Scientific Reports)
Abstract Tauopathies are a group of clinically and neuropathologically diverse neurodegenerative disorders defined by the abnormal aggregation of tau protein. While tau is normally soluble with limited secondary structure, pathological tau is characterized by hyperphosphorylation and assembly into fibrils which accumulate in neurons and glial cells in the central nervous system. The contribution of aberrant tau phosphorylation towards the pathogenesis of distinct disease manifestations is highly debated, however, it is posited that a hyperphosphorylation state influences aggregate formation due to tau’s inability to carry out its normal biological function(s). Due to the large number of potential phosphorylation sites on tau, determining the disease relevance of certain phosphorylation sites has remained challenging. Recent studies have demonstrated that tau phosphorylated at Thr217 can be detected in cerebrospinal fluid and plasma, is elevated in Alzheimer’s disease (AD) compared to other neurodegenerative diseases and is highly associated with hallmark pathologies. To further explore the neuropathological profile of this tau phosphorylation site in AD and other primary tauopathies, we generated and characterized a novel phosphorylation-dependent monoclonal antibody, 1F10. It is demonstrated that 1F10 is selective for tau phosphorylation at Thr217, and that the epitope for 1F10 is augmented in cultured cells overexpressing glycogen synthase kinase-3β. Moreover, 1F10 labelled neurofibrillary tangle-like inclusions in a mouse model of tauopathy and hallmark tau neuropathological lesions characteristic of AD and primary tauopathies but with differentiating antigenic profiles.